Effects of exercise and physical activity on gut microbiota composition and function in older adults (2023)
Background The characterization and research around the gut microbiome in older people emphasize microbial populations change considerably by losing the diversity of species. Then, this review aims to determine if there is any effect on the gut microbiota of adults older than 65 that starts an exercise intervention or improves physical activity level. Also, this review describes the changes in composition, diversity, and function of the gut microbiota of older subjects that had improved their physical activity level. Methods The type of studies included in this review were studies describing human gut microbiota responses to any exercise stimulus; cross-sectional studies focused on comparing gut microbiota in older adults with different physical activity levels—from athletes to inactive individuals; studies containing older people (women and men), and studies written in English. This review's primary outcomes of interest were gut microbiota abundance and diversity. Results Twelve cross-sectional studies and three randomized controlled trials were examined. Independently of the type of study, diversity metrics from Alpha and Beta diversity remained without changes in almost all the studies. Likewise, cross-sectional studies do not reflect significant changes in gut microbiota diversity; no significant differences were detected among diverse groups in the relative abundances of the major phyla or alpha diversity measures. Otherwise, relative abundance analysis showed a significant change in older adults who conducted an exercise program for five weeks or more at the genus level Conclusions Here, we did not identify significant shifts in diversity metrics; only one study reported a significant difference in Alpha diversity from overweight people with higher physical activity levels. The abundance of some bacteria is higher in aged people, after an exercise program, or in comparison with control groups, especially at the genus and species levels. There needs to be more information related to function and metabolic pathways that can be crucial to understand the effect of exercise and physical activity in older adults.